Blunt cerebrovascular injury following craniomaxillofacial fractures: A systematic review. (2nd August 2016) - Kelts, Gregory; Maturo, Stephen; Couch, Marion Everett; Schmalbach, Cecelia E.
Abstract : Objectives: Blunt cerebrovascular injury (BCVI) is a known sequela of high‐energy craniomaxillofacial (CMF) trauma and can result in stroke or death. The objective of this systematic review is to 1) identify CMF trauma patients who may benefit from BCVI screening and 2) describe the optimal diagnostic and treatment modalities. Study Design: Systematic review of the literature (1946–2013). Methods: An a priori study protocol was created using the Preferred Reporting Items for Systematic Reviews and Meta‐Analysis. The authors conducted a search of Ovid/Medline, PubMed, and Cochrane databases for articles related to BCVI and CMF fractures. All abstracts were reviewed, and data was extracted to determine the incidence of BCVI in the setting of CMF trauma. Individual fracture patterns were analyzed using descriptive statistics. Results: Twenty‐one studies met inclusion criteria. The overall incidence of CMF fracture‐associated BCVI was 0.45%. The majority of patients (86.6%) sustained BCVI in the setting of high‐energy trauma. The distribution of CMF fractures among BCVI patients was the mandible (12.5%), followed by the maxilla (11.8%). Computed tomographic angiography (CTA) was the most common diagnostic modality. A total of 63.1% of patients with BCVI were managed medically. The mortality among CMF patients with BCVI was 23.9%, and stroke rate was 47.1%. Conclusion: Blunt cerebrovascular injury is a rare but devastating complication of blunt trauma. The recommended screening modality is CTA, and the most common treatment is antiplatelet/anticoagulant medication. Mandibular and LeFort fractures were the most common isolated CMF injury associated with BCVI, highlighting the need for prospective trials to expand current screening criteria. Level of Evidence: N/A. Laryngoscope, 127:79–86, 2017